Low Concentration of Rapamycin Inhibits Hemangioma Endothelial Cell Proliferation, Migration, and Vascular Tumor Formation in Mice - Ningning Zheng, PhD; Xudong Ding, MD; Rabita Jahan (Elsevier, 2014)
Background: Vascular endothelial cell excessive proliferation is the main biological behavior of hemangioma. Rapamycin regulates the growth of endothelial cells by inhibiting mammalian target of rapamycin (mTOR). Thus hemangioma accompanied by excessive mTOR activation should be sensitive to rapamycin. We aimed to illustrate the effect of low-concentration rapamycin on hemangioma and provide a safe and effective drug therapy. Methods: Mouse hemangioendothelioma endothelial cells and Nu/Nu mice were used. Rapamycin was applied in a concentration from 1 nM to 20 nM. WST-1 cell proliferation and transwell migration assays were used to analyze vascular tumor proliferation and migration in vitro. Xenograft mouse models were used to test vascular tumor growth in vivo. Results: Low-concentration rapamycin (1 nM) inhibited hemangioendothelioma endothelial cell proliferation and migration in vitro and vascular tumor growth in vivo. The mechanism was decreased activation of the protein kinase B/mTOR/S6 ribosomal protein (S6) signaling pathway. Conclusions: Rapamycin used in vitro was analogous to low serum concentration rapamycin (7-16 nM) and also significantly inhibited the growth of hemangioma. These results demonstrate a low-toxic drug therapy for hemangioma and encourage continued development of rapamycin and its analogs for use in vascular tumor therapy.